Design, development, and performance study of a PWM based thermostat system for viscosity measurement - Md․Saidul Islam; Md․Sadequl Azam; Mahedi Hassan; Atish Bhathacharjee; Shahin Aziz (Results in Engineering)
Kinematic viscosity quantifies the inherent reluctance of a fluid to flow in response to gravitational forces. Viscosity is calculated by measuring the time it takes for a set volume of fluid to flow a specified distance by gravity through a capillary inside a calibrated viscometer at a strictly regulated temperature. Numerous researches have been done regarding this but the discussion about precision is absent. This study demonstrates the development and advancement of a digital thermostat control system for viscosity measurement incorporating pulse width modulation (PWM) technique in the heating module and rotator to achieve higher precise control. It comprises sensors and microcontroller-based technology to automatically regulate the temperature of bath liquid in a precise way. In this investigation, water and silicon oil both are used as heated fluids; nevertheless, the device is capable of functioning with any other alternative liquid as well. Based on the experimental findings, the tolerance of the bath temperature for water is 0.62 %, while for silicon oil it is 0.32 %. This article also discusses a comparison between using and not using PWM to showcase the influence on the precision of the thermo-control system of the bath. Incorporating PWM, excels in power management, increases accuracy, and customizable options.